PENGARUH GAME EDUKATIF WORDWALL TERHADAP PENGENALAN KONSEP BILANGAN ANAK USIA 5-6 TAHUN - Rida Dwi Kurniawati; Atin Fatimah; Kristiana Maryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine how the educational game Wordwall affects children at TK Putra II Serang aged between five and six years old in their ability to identify number concepts. The study uses a quasi-experimental method with a nonequivalent control group design. The research sample consisted of thirty children, fifteen of whom were in the experimental group and fifteen in the control group. Observation was the method used to collect data, and SPSS 24 was used to analyze the data using normality tests, homogeneity tests, and Independent Sample t-Test. According to the research findings, the average score of the experimental group increased from 25.33 to 34.20, while the control group increased from 24.13 to 31.00. The hypothesis test results showed a Sig. (2-tailed) value of 0.001 < 0.05, indicating that the use of the educational game Wordwall has a significant effect on children's ability to recognize numerical concepts at the age of 5 to 6 years. Therefore, Wordwall can be a useful and enjoyable teaching tool to support children's cognitive development. Keywords: Wordwall, educational game, number concepts, early childhood.